Accuracy of computer navigation in total knee arthroplasty: A prospective computed tomography-based study. (May 2020) - Hannan, Richard; Free, Matthew; Arora, Varun; Harle, Robin; Harvie, Paul
Highlights: Computer navigation aims to improve the accuracy of total knee arthroplasty surgery. We found close correlation between intraoperative measurements of alignment by the computer navigation system and postoperative CT-based measurements. For all measures of 3D alignment, the mean difference between intraoperatively recorded and postoperative CT-measured alignment was 1.55.°. The mean difference in whole limb coronal alignment between intraoperative and postoperative measurements was 2.34.°. Abstract: Introduction: Evidence now exists advocating the use of computer navigation in total knee arthroplasty (TKA). Despite the introduction of new navigation systems into clinical practice no evidence currently exists showing independent verification of their accuracy. The aim of this study was to validate the in vivo accuracy of the Exactech Guided Personalised Surgery (GPS) computer navigation system using a validated computed tomography (CT) measurement of alignment. Method: Consecutive patients who underwent TKA using the GPS Navigation System at our institution were prospectively recruited. Intraoperative parameters of 3D alignment as measured by the GPS navigation system were recorded and compared against the postoperative measurements of alignment measured using the Perth CT Protocol to assess the accuracy of the GPS navigation system. Results: 29 consecutive patients (13 male, 16 female) who underwent TKA were prospectively recruited. Overall, for all measures of 3D alignment the mean difference between intraoperatively recorded and postoperative CT-measured alignment was 1.55° ± 0.22° (95% confidence interval). Individual measurement differences in the femoral prosthesis were: coronal alignment 1.64° ± 0.52°; flexion 2.07° ± 0.55°; rotation 1.38° ± 0.33° Differences in the tibial prosthesis were: coronal alignment 2.03° ± 0.53°; slope 1.14° ± 0.39° The whole limb coronal alignment difference was 2.34° ± 0.83° Conclusion: The Exactech GPS Navigation system is very accurate with a high concordance between intraoperative and postoperative measures of alignment and prosthesis positioning. We therefore confidently validate the system and support its continued use in clinical practice. Other navigation systems should undergo a similar validation process.